The Effect of Psych-education on Fear of Childbirth and Postpartum Outcome: Systematic Review and Meta Analysis - Zulfıyya Nuralıyeva; Ayşenur Turan; Aysu Yıldız Karaahmet (Genel Tıp Dergisi)
Aim: This systematic review and meta-analysis study aimed to investigate the effects of psychoeducation on fear of childbirth and postpartum outcomes. Methods: Literature search was conducted in PubMed, CINAHL, Scopus and Science Citation Index (Web of Science) until December 2022. This work is based on the recommendations of the Cochrane guidelines. The data were analyzed using the Review Manager computer program (Version 5.3). Results: Eight randomized controlled trials were included in the meta-analysis: all 8 studies were combined for fear of childbirth. In the meta-analysis, it was seen that psychoeducation decreased the fear of birth (MD: 10.18 95% CI: 9.32 to 11.05, Z = 23.09, p < 0.00001) in pregnant women, when the anxiety and depression rate (SMD: -0.36 95% CI: -0.57 to -0.15, Z = 3.34, p=0.0008) were examined, it was seen that there was no difference in depression, it decreased the cesarean section (SMD: -0.35 95% CI: -0.49 to -0.22, Z = 5.19, p<0.00001) rate and increased the self-efficacy (SMD: 0.38 95% CI:0.25 to 0.51, Z =5.58 p <0.00001) rate. Conclusion: This study provides sufficient evidence that psychoeducation is effective in reducing fear of childbirth, anxiety, and cesarean section rates, while increasing self-efficacy.